Relationship between SARS-CoV2 infection and the development of chronic non-communicable diseases - Hreçay , Alessandra Naomi da Lus; Felipus, Lucas Cavalheri; Veiga, Natan; Locatelli , Claudriana (Seven Editora, 2023)
COVID-19, a disease triggered by the SARS-CoV-2 coronavirus, emerged in Wahuan and became a global pandemic abruptly, causing great tensions around the world. The composition of the virus is based on a single-stranded RNA viral structure that uses  the spike protein  (S-spike) to bind to the ECA2 receptor in human cells. Symptoms can range from mild, moderate or severe symptoms and infection can lead to systemic complications and chronic sequelae. In addition, the disease can be classified into asymptomatic, acute, subacute, and post-covid syndrome when symptoms persist for more than 12 weeks. Sequelae can include heart, lung, neurological and renal problems, which can affect the quality of life of infected patients. The prognosis is motivated by the severity of the infection and the pre-existing health status. Preventive measures such as strict hygiene, social distancing, mask-wearing and vaccination are of utmost importance to mitigate the spread of the virus. However, long-term medical follow-up is necessary to monitor and treat complications arising from the infection. DOI:https://doi.org/10.56238/globalhealthprespesc-048